Developing adaptive hypermedia system based on learning design level B with rules for adaptive learning activities - Anh, Nguyen Viet; Ha, Nguyen Viet; Dam, Ho Si (VNU Journal of Science: Natural Sciences and Technology; Vol 25 No 1, 2009)
Abstract